Kinetic Modeling of the Suspension Copolymerization of Styrene/Divinylbenzene with Gel Formation - Gonçalves, Miguel A.D. (2011)
Experimental and theoretical studies concerning the suspension copolymerization of styrene with divinylbenzene are reported. Experiments were carried out in a batch stirred reactor, at 1.2 dm3 scale, and extended beyond gelation in order to synthesize insoluble material. Looking for real time information concerning the building process of such materials, these polymerizations were In-line monitored using a FTIR-ATR immersion probe. Polymer samples collected before and after gelation were Off-line characterized using a SEC/RI/MALLS system allowing the measurement of monomer conversion, average molecular weights, MWD and also the z-average radius of gyration. The weight fraction of insoluble material (gel) was measured for samples with different reaction times. The experimental program has included the study of the influence of key polymerization parameters on the dynamics of gelation and some properties of the resulting networks, namely the initial mole fraction of crosslinker and the initial proportions between monomers and inert diluent. Variable n-heptane/toluene mixtures were used within this purpose. These experimental observations were complemented with theoretical studies using a general kinetic approach allowing the prediction of MWD and z-average radius of gyration before and also after gelation. Comparison of the experimental measurements with these predictions is being exploited to develop modeling tools useful for the design of operating conditions allowing the improvement of the performance of the final products.